Extending the Utility of the Bartoli Indolization: Synthesis of Marinoquinolines C and E - Lindsay, Ashley C.; Sperry, Jonathan (Synlett, 2013)
A short synthesis of marinoquinolines C and E has been achieved. The synthetic route involves an ipso nitration of an electron-deficient boronic acid, the first example of a Bartoli indolization on a nitroquinoline and Suzuki coupling between 2-chloropyrroloquinoline and two separate MIDA boronates.
Keywords: marinoquinolines; ipso nitration; Bartoli indolization; Suzuki cross-coupling; pyrroloquinoline